Nutritional Content, Antioxidant Activity, and Amino Acid Properties of Mungbean (Vigna radiata) Enteral Formulation for Dementia - Aulia, Salma Shafrina; Wildan Alfira Gusrianto; Cleonara Yanuar Dini; Lini Anisfatus Sholihah; Satwika Arya Pratama; Fista Utami; Muhammad Alfid Kurnianto (Media Gizi Indonesia, 2026)
Mung bean (Vigna radiata) is a widely consumed legume rich in high-quality protein. The development of enteral formulas using mung beans as a raw material represents a promising alternative nutritional approach for dementia patients with impaired oral intake. This study aimed to investigate the effects of different pre-treatment methods on the nutritional density, physical properties, and amino acid profile of mung bean–based enteral formulas. Three formulations were prepared: boiled mung bean blenderized formula (FA), steamed mung bean blenderized formula (FB), and powdered mung bean blenderized formula (FC). Proximate composition and viscosity were assessed in all formulas. The formula with the highest protein and most favorable proximate profile was further analyzed for amino acid composition and antioxidant activity. Pre-treatment significantly affected energy, protein, fat, carbohydrate, and water content (p <0.05) but not viscosity. The powdered mung bean formula exhibited the highest protein concentration, with glutamic acid (5340.93 µg/g) and isoleucine (3033.71 µg/g) being the most abundant amino acids. It also demonstrated antioxidant activity with an IC50 value of 60,719.07 mg/L.This study provided that the powdered mung bean formula has potential to become an enteral formulation for dementia.